(untitled) (IAHS Medical Journal, 2026)
Background: Colorectal Carcinoma (CRC) demonstrates geographic variations in presentation. Recent data on clinico-pathological characteristics from Bangladesh remains limited. This study aimed to describe the demographic, risk factors and histopathological profile of colorectal adenocarcinoma patients at a tertiary hospital in Bangladesh. Materials and methods: A cross-sectional observational study was conducted in the Department of Pathology, Chittagong Medical College, Bangladesh, from March 2021 to December 2022. Purposive sampling included 49 surgically resected, histopathologically confirmed primary colorectal adenocarcinoma specimens. Data on demographics, risk factors (Smoking, alcohol, family history) and tumor characteristics (Size, site, morphology) were collected through patient interviews using a structured case record form. Histopathological examination (H&E staining) determined subtype, grade, T stage (Tumour stage) and N stage (Involvement of lymph node). Results: The mean age was 46.63 ± 13.4 years, with 79.6% of patients <60 years. Male predominance was observed (63.3%), 49% reported smoking, while alcohol consumption was minimal (4.1%). Only 16.3% had a positive family history. Most tumors were ≤5 cm (61.2%, mean 5.16±2.63 cm), with ulcerative growth (44.9%) being most common. The sigmoid colon was the predominant site (36.7%). Conventional adenocarcinoma comprised 89.8% of cases; most were low-grade (87.7%) and moderately differentiated (67.3%). Pathologically, T3 invasion was most frequent (55%), followed by T2 (28.6%). Most tumors (63.3%) had no nodal involvement (N0). Conclusion: CRC in this Bangladeshi cohort presents at a significantly younger age than in Western populations, with a high smoking prevalence and sigmoid colon predilection. Despite frequent deep mural invasion (T3) a majority showed no nodal metastasis. These findings highlight unique regional trends, underscoring the need for early screening initiatives and focused research into local risk factors like smoking. IAHS Medical Journal Vol 8(1), June 2025; 88-93